The association between weight-adjusted-waist index and total bone mineral density in adolescents: NHANES 2011–2018 - Wang, Xiaohua; Yang, Shuo; He, Gansheng; Xie, Lin (Frontiers in Endocrinology, 2023)
Abstract Introduction：The weight-adjusted waist index (WWI) serves as an innovative obesity measure, seemingly surpassing body mass index (BMI) and waist circumference (WC) in evaluating lean and fat mass. This study aimed to explore the relationship between WWI and total bone mineral density (BMD) in US adolescents Methods: This population-based study investigated adolescents aged 8-19 years with comprehensive WWI and total BMD data from the National Health and Nutrition Examination Survey (NHANES) 2011-2018. WWI was computed by dividing WC by the square root of body weight. Weighted multivariate linear regression and smoothed curve fitting were employed to examine linear and non-linear associations. Threshold effects were determined using a two-part linear regression model. Additionally, subgroup analyses and interaction tests were conducted. Results: This population-based study encompassed 6,923 US adolescents aged 8-19 years. Multivariate linear regression analysis revealed a significant negative association between WWI and total BMD [-0.03 (-0.03, -0.03)]. This negative relationship persisted across all subgroup analyses, including gender, age, diabetes status, and race. Furthermore, a non-linear relationship and saturation effect between WWI and total BMD were identified, with an inflection point at 9.88 cm/√kg. Conclusions: Our research demonstrated a notable negative relationship and saturation effect between WWI and total BMD among US adolescents.